Hubungan penggunaan smartphone dengan fungsi penglihatan pada mahasiswa Fakultas Kedokteran Universitas Sam Ratulangi Manado angkatan 2016 - Bawelle, Christo F.N.; Lintong, Fransiska; Rumampuk, Jimmy (Universitas Sam Ratulangi, 2016)
Abstract: Smartphone is a kind of cellular phone that has high capability, and worked by radiate the electromagnetic radiation of radio frequency. The eye is visual sense that can capture the reflected light beam of an object. The increased of using smartphone nowadays made the community worry about the effects of smartphone radiation for health especially on the visual function. Objective: To know the correlation between the duration of using smartphone with visual function, and to know the correlation between the intensity of using smartphone with visual function in students of Medical Faculty Unsrat 2016 generation. Method: The research conducted was analytic survey with used cross sectional approach, the research conducted on Oktober 2016 at Department of Physics in Medical Faculty of Manado Sam Ratulangi University. Result: Based on the analysis result by Chi Square test obtained p= 0,033 which means there was the correlation between the duration of using smartphone with the visual function, and there was no correlation the between intensity of using smartphone with visual function with score p=0,786. Conclusion: There was a correlation between the duration of using smartphone with visual function in students of Medical Faculty Manado Sam Ratulangi University. There was no correlation between the intensity of using smartphone with visual function in students of Medical Faculty Manado Sam Ratulangi University.Keywords: smartphone, visual functionÂ Abstrak: Smartphone merupakan sejenis telepon seluler yang mempunyai kemampuan tinggi, dan bekerja dengan cara memancarkan sejenis radiasi elektromagnetik radio frekuensi. Mata merupakan indra penglihatan yang dapat menangkap berkas cahaya yang dipantulkan dari sebuah benda. Peningkatan penggunaan smartphone di era sekarang ini menimbulkan kekhawatiran pada masyarakat tentang efek radiasi sinar smartphone terhadap kesehatan terutama fungsi penglihatan. Tujuan: Untuk mengetahui hubungan antara lama penggunaan smartphone dengan fungsi penglihatan, dan untuk mengetahui hubungan antara intensitas penggunaan smartphone dengan fungsi penglihatan pada mahasiswa Fakultas Kedokteran Unsrat angkatan 2016. Metode: Penelitian yang dilakukan bersifat survei analitik dengan menggunakan pendekatan cross sectional, penelitian dilakukan pada bulan Oktober 2016 di Bagian Fisika Fakultas Kedokteran Universitas Sam Ratulangi Manado. Hasil: Berdasarkan hasil analisis dengan uji Chi Square diperoleh p=0,033 yang artinya ada hubungan lama penggunaan smartphone dengan fungsi penglihatan. Tidak terdapat hubungan secara statistik antara intensitas pengguanaan smartphone dengan fungsi penglihatan dengan nilai p=0,786. Simpulan: Ada hubungan antara lama penggunaan smartphone dengan fungsi penglihatan pada Mahasiswa Fakultas Kedokteran Universitas Sam Ratulangi. Tidak ada hubungan antara intensitas penggunaan smartphone dengan fungsi penglihatan pada Mahasiswa Fakultas Kedokteran Universitas Sam Ratulangi.Kata kunci: smartphone, fungsi penglihatan